An insight into biosecurity plant-disease diagnostics at MPI - Taylor, Robert K.; Toome-Heller, Merje; Ho, Wellcome W.H.; Alexander, Brett J.R. (New Zealand Plant Protection, 2019)
The Mycology and Bacteriology team of the Ministry for Primary Industries’ Plant Health and Environment Laboratory is responsible for the identification and verification of all suspected exotic, new, and emerging pathogens affecting plants and the environment in New Zealand. We work in an applied diagnostic environment where results can have significant implications for biosecurity. Sample submissions often result in detection of new to New Zealand fungi and bacteria on plants for which information on fungal and bacterial associations is generally sparse. The complexity of testing required is quite varied with samples being submitted from post entry quarantine (looking for a known pathogen using specific tests), border or surveillance (unknown pathogens requiring multiple tests), or a biosecurity response (scaling up to test large numbers, identification resolution required to strain level). Applied test methods depend largely on the sample type and consist of morphological identification, biochemical testing, pathogenicity testing, serological and molecular techniques, including high throughput sequencing. A profile of our diagnostic work and the most commonly detected taxa and host associations are presented.